The effect of ladder drill V-pattern and snake jump exercises on the agility of basketball athletes - Ramadhany Hananto Puriana; Shandy Pieter Pelamonia; Kristoforus Ado Aran; Suryansah Suryansah; Santoso Noto Nugroho; Muh. Rizaldi; Naufal Alannuri; M. Bunayya Rezaldi; Abdul Agil Mubarok; M. Azyan Hariz; Sayid Hadam Zikrillah Al Idrus (Jurnal Porkes, 2023)
There are many problems with the average player's movement being stiff, not fast and not agile when defending so that the opponent can easily pass them by. The aim of this research is to improve the agility abilities of men's basketball athletes in the city of Kediri. Quantitative research materials and methods use a pre-experimental research design, the two group pretest posttest design, because it consists of two groups (there is no control group) and the research process is carried out in groups. three stages. The subjects of this research were 15 men's basketball athletes who were in TC (training) in Kediri City for pre-porprov preparations in East Java. The results of data analysis in the normality test using Shapiro-Wilk show that the data is normally distributed. The prerequisite test uses the lavender test. Data comes from a homogeneous population. Hypothesis testing using pairs, sample T-Test with a significance level (< 5%) obtained a value of 0.005 for biomotor agility ability. Conclusion: Based on statistical results, it can be concluded that ladder drill training has a significant influence on increasing agility abilities.